Electrical transport properties of TiO2/MAPbI3 and SnO2/MAPbI3 heterojunction interfaces under high pressure. Issue 5 (23rd January 2023) - Li, Yuqiang; Li, Yuhong; Zhang, Qiang; Liu, Xiaofeng; Li, Yuanjing; Xiao, Ningru; Ning, Pingfan; Wang, Jingjing; Zhang, Jianxin; Liu, Hongwei
Abstract : The electrical transport properties of SnO2 (TiO2 )/MAPbI3 (MA = CH3 NH3 + ) heterojunction interfaces are investigated from ambient pressure to 20 GPa. Abstract : The electrical transport properties of SnO2 (TiO2 )/MAPbI3 (MA = CH3 NH3 + ) heterojunction interfaces are investigated from ambient pressure to 20 GPa, and the transport properties are calculated by physical parameters such as trap energy density, binding energy, and charge transfer driving force and defect. Based on the partial density of states (PDOS) of the SnO2 /MAPbI3 heterojunction interface MAI-termination and PbI2 -termination, greater charge transfer driving force and higher binding energy are observed, obviously showing the SnO2 -based heterojunction is more stable. The SnO2 /MAPbI3 heterojunction interface possesses stronger electrical transport ability and is less prone to capture electrons compared with the TiO2 /MAPbI3 heterojunction interface. The differential charge density spectrum shows that the density is lower in the trap energy level of SnO2 /MAPbI3, whilst the effect of the charge transfer defect is weaker owing to the trap energy level only existing in SnO2 . The SnO2 /MAPbI3 heterostructure interface is less prone to capture electrons. The greater electron concentration difference is attributed to oxygen vacancy (Vo0 ) in the SnO-like environment, resulting in superior electron transport ability compared with the TiO-like environment.